THU0411 Drug Holiday during Biological Therapy - A Patient Perspective. (10th June 2014) - Kosevoi, A.; Berghea, F.; Bojinca, V.; Opris, D.; Constantinescu, C.; Abobului, M.; Groseanu, L.; Saulescu, I.; Borangiu, A.; Negru, M.; Balanescu, A.; Predeteanu, D.; et al.
Abstract : Background: Biologic therapy is extensively used in various rheumatic disease adding a plus of efficacy to classical DMARDS. Standardized regimes are based on continuous use of biologics but for various reasons (e.g. health insurance issues, patients' concerns related to safety of long term use or a surgical emergency) a drug holiday might come into discussion. While rheumatologists' reasons to support or not this holiday are widely presented in the literature little is known about the patients' beliefs and attitudes in this matter. Objectives: To evaluate the rheumatic patients' beliefs and attitudes regarding a potential drug holiday during biologic treatment. Methods: A structured questionnaire was developed to capture demographic data, personal experience and acceptance of biologic therapy, level of knowledge about possible drug holiday, personal beliefs and attitudes regarding such regime. Rheumatic patients receiving biologic treatment have been invited to answer the questionnaire. SPSS 19.0 have been used to perform statistical analysis. Data are presented in mean (sd) format; a p<0.05 was considered significant. Results: A number of 69 subjects accepted to participate in this study. Demographic data revealed: age 51.6 (13.6) years, sex ratio (F:M) – 1.3:1, 69.6% suffering from Rheumatoid arthritis and 30.4% from spondilarthritis, duration of biologic therapy: 34.67 (27.5) months. 44.9% of the subjects already considered of the possibility of a drug holiday (no difference between gender, living area or education based groups). 75.0% believe that such a holiday will produce a "totally negative" and a "mainly negative" impact on the control of disease. Those who believe this holiday will have a greater impact are the same who predict a predominant negative impact – Pearson correlation index: o, 42. A small minority (14.7%) declared them as being favorable to such a holiday, however these answers went mainly from those who believe this holiday will have a small impact on the control of disease and are ready to try this in the near future. 82.7% of the subjects expect their doctor to open such a subject. Those who are not favorable to such a holiday are ready to pay extra for the treatment (20.6%) or to receive a less expensive drug (75.0%). Conclusions: There is a great need for research regarding the potential effects of drug holiday during the biologic therapy and to respond to various concerns patients do have. A large proportion of patients have negative feelings concerning this possibility. Those patients (not so many) that feel they control the disease are the same who are ready to try this change – this raise the question whether or not the patients follow their treatment because they are more scared than informed of their disease. A very large proportion of patients are ready to accept a less expensive drug in exchange not to start a drug holiday – while biologic biosimilars already offer this opportunity it might be interesting to explore the consequences of such a decision. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3322